Investment Decision-Making Through Technical Analysis of LQ45 Stocks Movements - Sophia Andina; Ida Busnetty; Agustina Suparyanti (International Journal of Economics Accounting and Management, 2025)
Investment decisions in financial markets often face challenges during periods of high price fluctuation and inconsistent trends. This study investigates the role of technical analysis in guiding short-to medium-term investment strategies by evaluating the effectiveness of Bollinger Bands and the Stochastic Oscillator. The research focuses on four stocks from the LQ45 Index – Bank Rakyat Indonesia, Sumber Alfaria Trijaya, Adaro Energy Indonesia, and Unilever Indonesia – analyzing their price movements throughout the 2024 period. A quantitive descriptive method was employed to proccess daily stock price data and identify signals related to overbought and oversold market conditions. The findings reveal that the combination of both indicators generates reliable signals for anticipating trend reversals and supports informed buy or sell actions. The study confirms that technical analysis provides meaningful insights for investors to manage market fluctuations effectively. The conclusion highlights that applying technical indicators consistently can enhance decision-making accuracy, particularly for investors aiming to optimize entry and exit timing. This research contributes to the understanding of how chart-based tools can be integrated into practical investment strategies in dynamic market environments